2021
DOI: 10.1002/cmdc.202000996
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chronic Inflammation in Various Diseases and Anti‐inflammatory Therapies Containing Natural Products

Abstract: Chronic inflammation represents a long-term reaction of the body's immune system to noxious stimuli. Such a sustained inflammatory response sometimes results in lasting damage to healthy tissues and organs. In fact, chronic inflammation is implicated in the development and progression of various diseases, including cardiovascular diseases, respiratory diseases, metabolic diseases, neurodegenerative diseases, and even cancers. Targeting nonresolving inflammation thus provides new opportunities for treating rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 253 publications
(153 reference statements)
0
14
0
Order By: Relevance
“…3-(3-Allyl-4-hydroxyphenyl)-5-hydroxy-7-(methoxymethoxy)-4Hchromen-4-one (19). Following the general procedure, 18 (400 mg, 1.00 mmol) was converted to General Procedure for the Synthesis of 3′-Allyl-4′-methoxyisoflavones 20 and 26.…”
Section: -(4-(allyloxy)phenyl)-7-(methoxymethoxy)-4h-chromen-4-one (22a)mentioning
confidence: 99%
See 1 more Smart Citation
“…3-(3-Allyl-4-hydroxyphenyl)-5-hydroxy-7-(methoxymethoxy)-4Hchromen-4-one (19). Following the general procedure, 18 (400 mg, 1.00 mmol) was converted to General Procedure for the Synthesis of 3′-Allyl-4′-methoxyisoflavones 20 and 26.…”
Section: -(4-(allyloxy)phenyl)-7-(methoxymethoxy)-4h-chromen-4-one (22a)mentioning
confidence: 99%
“…Both are rich sources of bioactive secondary metabolites, among which isoflavonoids stand out. Isoflavonoids share a 3-arylchromone skeleton and are often phytoestrogens, i.e., they show biological activity similar to estrogen, , apart from other bioactivities, , such as anti-inflammatory activity, anticancer activity, antimicrobial activity, and activity against neurodegenerative diseases. The estrogenic activity of isoflavones in many edible plants, such as soybeans, has been linked to beneficial as well as detrimental effects on human health …”
Section: Introductionmentioning
confidence: 99%
“…Such inflammatory mediators and interconnected pathways are mainly involved in the underlying mechanisms of the inflammatory state [ 42 ]. Several studies show that phytochemicals are multi-target agents that effectively represent their anti-inflammatory activities through underlying cellular mechanisms against different diseases associated with chronic inflammation [ 43 ]. In the phytochemical context, it has been reported that polydatin is a potent anti-inflammatory plant secondary metabolite [ 44 ], beneficially promoting miR-200a expression to regulate the Kelch-like ECH-associated protein 1 (Keap1)/nuclear factor E2-related factor 2 (Nrf2) antioxidant axis.…”
Section: Pharmacological Mechanisms Of Polydatinmentioning
confidence: 99%
“…It is usually beneficial for the host to initiate healing and promote tissue recovery. Once acute inflammation fails to resolve the damage, inflammation will progress to the chronic stage—a low-grade inflammation that persists for weeks, months, or even years [ 3 ]. The World Health Organization (WHO) ranks chronic diseases as the greatest threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) ranks chronic diseases as the greatest threat to human health. Chronic inflammation is related to many human diseases, including diabetes, rheumatoid arthritis, atherosclerosis, asthma, neurodegenerative disorders, and cancer [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%